Extraction and screening of various hydrolases from Malaysian channel catfish (ictalurus punctatus) viscera - Mahmod , Safa Senan; Yusof, Faridah; Jami, Mohammed Saedi (2014)
Malaysia is a large producer of fish industry estimated to be 1.5million tonnes every year. 35-50% of the fish weight is its viscera, which is usually disposed into the landfills or sea leading to massive environmental problems. However, various hydrolases can be extracted from this highly potential by-product source. In this study, protease, lipase, α-amylase and cellulase activities were studied. Protein concentration of the whole viscera of Ictalurus punctatuswas 0.798596 mg/mL, protease gives the highest specific activity among the hydrolases (13.57 U/mg), cellulase was (1.43 U/mg), lipase (1.425 U/mg) and the α-amylase was (0.689 U/mg).